Upaya Guru Menerapkan Metode Pembelajaran Resitasi Read Challenge Guna Menumbuhkan Minat Membaca Siswa Kelas V Sekolah Dasar - Kusumaningrum, Erliana Vivi; Kironoratri, Lintang; Hidayati, Nur Alfin (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
The aim of this research is to find out how the fifth grade teacher's efforts apply the recitation read challenge learning method to foster interest in reading in fifth grade students at SD N 2 Mijen. This research uses descriptive qualitative methods. The subjects in this research focused on fifth grade students who had little interest in reading. The data collection techniques for this research are observation, interviews and documentation. The results of this study show that students are more interested in reading after using the recitation learning method by giving students reading assignment materials and holding them accountable for their assignments with reading challenges. In the disclosure of the class V teacher, class V students' interest in reading began to increase after implementing the recitation read challenge learning method. From the results of student evaluations it became 93% in the complete category, where out of 25 students, only 2 students needed additional guidance from the teacher. So it can be concluded that growing interest in reading was said to be successful after the fifth grade teacher implemented the recitation read challenge learning method.